A kind of aqueous viologen compound liquid flow battery negative electrode slurry
Patent Information
- Application Number
- CN202611068202.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]发明目的:本发明目的是提供一种水系紫精类化合物液流电池负极浆料,通过引入非金属掺杂的多孔碳材料构建负极浆料体系,有效解决了现有紫精体系液流电池长循环过程中紫精类化合物副反应导致粘度升高引起的高浓度紫精体系传质恶化的问题,本发明负极浆料能够大幅提高体系中负极活性物质的氧化还原反应速率,降低二聚等副反应发生概率,减缓电解液粘度变化,优化传质,从而显著提升液流电池的能量密度、长循环稳定性及电化学反应效率
[0019]有益效果:相比于现有技术,本发明具有如下显著的优点:本发明负极浆料作为可流动电极介质,浆料结构能够改善反应器尺度上的流体分布与物质传输,从而缓解固定多孔电极所固有的局部浓差和滞流现象。(2)以介孔为主的多孔结构可使紫精类化合物单分子吸附,抑制MV+·的局部富集,降低二聚及其他副反应发生的概率,从而减缓电解液粘度变化,优化传质。(3)浆料中均匀分散的多孔碳颗粒可提供丰富且可接近的催化活性位点,增强对紫精类化合物的吸附与催化作用,并且浆料电极中持续更新的反应界面与更短的传输路径有助于促进电荷转移和离子扩散,降低极化,提高双电子反应的可逆性,并最终提升电池能量密度与倍率性能。本发明负极浆料实现了对副反应的抑制、传质过程的优化以及电池性能的提升。
Smart Images

Figure CN123017992A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a negative electrode slurry for an aqueous violane-based compound flow battery. Background Technology
[0002] Among numerous energy storage technologies, redox flow batteries have attracted widespread attention due to their ability to independently scale up power and capacity, high operational safety, long cycle life, and suitability for large-scale stationary energy storage. Aqueous organic redox flow batteries (AORFBs), in particular, are considered an important alternative to traditional metal-based systems due to the advantages of tunable organic redox molecules, abundant resources, and environmental friendliness. Among many organic redox active materials, viologen compounds are considered highly promising anode electrolyte active materials due to their low redox potential and large molecular engineering control space. Methyl viologen (MV) and its derivatives can theoretically undergo two consecutive one-electron reduction processes, thus achieving two-electron energy storage and significantly improving the theoretical capacity and energy density of the battery. However, for viologen-based flow batteries with high concentrations of active materials, the two-electron viologen system is more susceptible to MV degradation under localized high-concentration conditions compared to single-electron systems. +· Side reactions such as free radical dimerization lead to a gradual decrease in battery capacity retention and long-cycle stability. Furthermore, due to the strong intermolecular interactions of free radical dimers, the capacity retention (MV) decreases with cycling. +· The continued dimerization and polymerization of viologen and its derivatives further enhance intermolecular interactions, leading to a gradual increase in electrolyte viscosity. This hinders mass transfer and diffusion, intensifies polarization, and severely limits its practical application. This problem not only weakens electrochemical reversibility but also reduces effective diffusion capacity and deteriorates electrolyte rheological properties, becoming a key bottleneck for achieving both high power and long lifespan in high-concentration viologen flow batteries. Furthermore, traditional flow battery devices use fixed graphite felt electrodes, which suffer from uneven pore distribution and limited accessible active sites. In high-concentration viologen flow batteries, these structural features easily induce non-uniform distribution and local stagnation of active materials, resulting in locally enriched MV. +· When there are fewer active sites, the redox reaction of the derivatives is slower, causing more free radicals to undergo polymerization. This not only increases the probability of dimerization and other side reactions and exacerbates changes in electrolyte viscosity, but also intensifies electrochemical polarization and affects the long-cycle performance of the battery.
[0003] Current research on viologen-based flow batteries mainly focuses on improving the solubility, reversibility, and structural stability of viologen systems in neutral aqueous electrolytes through molecular design and electrolyte engineering. However, no solutions have been proposed to address the technical problems of localized enrichment of viologen compounds, worsening of side reactions, and deterioration of mass transfer due to increased viscosity. Summary of the Invention
[0004] Purpose of the Invention: The purpose of this invention is to provide an aqueous viologen-based compound negative electrode slurry for flow batteries. By introducing non-metallic doped porous carbon materials to construct the negative electrode slurry system, this invention effectively solves the problem of mass transfer deterioration in high-concentration viologen systems caused by increased viscosity due to viologen-based compound side reactions during long-cycle operation of existing viologen-based flow batteries. The negative electrode slurry of this invention can significantly increase the redox reaction rate of the negative electrode active material in the system, reduce the probability of side reactions such as dimerization, slow down electrolyte viscosity changes, and optimize mass transfer, thereby significantly improving the energy density, long-cycle stability, and electrochemical reaction efficiency of flow batteries.
[0005] Technical solution: The aqueous viologen-based compound flow battery negative electrode slurry of the present invention is prepared by mixing non-metallic doped porous carbon material, viologen-based compound, supporting electrolyte, pH modifier and dispersant in an aqueous medium; the non-metallic doped porous carbon material is phosphorus-doped porous carbon material, oxygen-doped porous carbon material or phosphorus-oxygen co-doped porous carbon material.
[0006] In the negative electrode slurry, the molar concentration of the viologen compound is 0.6~1.0M, preferably 0.6M; the molar concentration of the supporting electrolyte is 1.0~1.5M, preferably 1.5M; the molar concentration of the pH modifier is 0.05~0.06M, preferably 0.06M, to maintain a neutral environment; the dispersant accounts for 0.3~0.5wt% of the mass of the aqueous medium, preferably 0.3wt%; and the non-metallic doped porous carbon material accounts for 1.5~2.5wt% of the mass of the aqueous medium, preferably 2wt%.
[0007] The viologen compound is 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen (synthesized using the method reported in the literature *ScreeningViologen Derivatives for Neutral Aqueous Organic Redox Flow Batteries*) or methyl viologen. The supporting electrolyte is KCl or NaCl. The dispersant is xanthan gum. The pH modifier is NaHCO3.
[0008] The ultrasonic time during the preparation of the slurry is 60-80 minutes, and the ultrasonic power is 300-400W.
[0009] The non-metal-doped porous carbon material is prepared by the following method, specifically including the following steps:
[0010] (1) Wash, crush, sieve and dry the waste biomass to obtain biomass raw material that has lost its surface water;
[0011] (2) The obtained biomass raw materials are mixed with activator and carbonized under inert gas protection. After treatment, the raw materials are washed and dried to obtain porous biochar.
[0012] (3) The porous biochar is mixed with a non-metallic dopant source and added to water. It is first dried in a vacuum environment and then carbonized at high temperature under inert gas protection. After carbonization, it is washed and dried to obtain a non-metallic doped porous carbon material.
[0013] In step (1), the waste biomass is one of lignin, macadamia nut shell, coconut shell, peanut shell or walnut shell; preferably lignin; the drying temperature is 105~110℃ and the sieve mesh is 100~200 mesh.
[0014] In step (2), the activator is one of KOH, KHCO3 or KCl, preferably KOH; the mass ratio of the activator to the biomass is 1:0.5~1, preferably 1:1.
[0015] In step (3), the non-metallic dopant source is 1-hydroxyethylidene-1,1-diphosphonic acid and / or hydrogen peroxide; and the mass ratio of the non-metallic dopant source to the porous biochar is 0.22~1.05:1.
[0016] In steps (2) to (3), the carbonization temperature is 850 to 900°C and the carbonization time is 3 to 4 hours.
[0017] The carbon material in the negative electrode slurry of this invention uses waste biomass (such as lignin, macadamia nut shells, etc.) as raw material. These materials themselves have a natural porous structure and surface functional groups. Through a high-temperature pyrolysis process, their specific surface area can be further increased and their porous structure can be controlled to form porous biochar with physicochemical adsorption capabilities. The porous structure of the biochar enables it to effectively adsorb oligol compounds, reducing the shuttle effect of oligol compounds diffusing to the positive electrode, thereby improving the cycle stability and energy efficiency of the flow battery. The activator (KOH) initiates chemical activation at high temperature, further regulating and optimizing the pore structure of the biochar and increasing its specific surface area, enabling it to more effectively adsorb and catalyze oligol compounds in the negative electrode slurry, avoiding the performance loss caused by the limited number of catalytic sites and narrow mass transfer channels in traditional flow batteries. Non-metallic element doping sources (1-hydroxyethylidene-1,1-diphosphonic acid, hydrogen peroxide) are introduced into biochar and formed into a non-metallic element co-doped catalyst through high-temperature calcination. Due to its extremely high catalytic activity and uniform dispersion, it can significantly improve the redox reaction kinetics of viologen compounds and accelerate the battery charging and discharging process.
[0018] The mesoporous hierarchical pore structure and oxygen-containing functional groups on the surface of the negative electrode slurry of this invention effectively adsorb viologen compounds through physicochemical processes, significantly suppressing the diffusion and shuttle effects caused by the small molecular size. Furthermore, the mesoporous hierarchical pore structure allows for effective dispersion of viologen compounds, achieving high utilization of active sites. Simultaneously, the non-metallic doped catalytic sites not only enhance the two-electron redox reaction kinetics of viologen compounds but also alter the electron distribution on the carbon material surface, forming an electron-rich region, thereby accelerating interfacial electron transfer and improving battery polarization. These synergistic effects effectively suppress side reactions such as dimerization caused by excessively high local concentrations of viologen compounds, mitigate electrolyte mass transfer problems caused by changes in electrolyte viscosity, and significantly improve battery performance and long-cycle stability. The negative electrode slurry obtained by this invention is a liquid suspension that can be applied to both dissolved and undissolved methyl viologen compound flow batteries, overcoming the limitations of traditional aqueous organic flow batteries, such as slow two-electron transfer kinetics and severe side reactions like dimerization.
[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: The negative electrode slurry of the present invention is a flowable electrode medium. The slurry structure can improve the fluid distribution and mass transport at the reactor scale, thereby alleviating the local concentration difference and stagnation phenomenon inherent in fixed porous electrodes. (2) The porous structure dominated by mesoporous structures can enable the adsorption of viologen compounds as single molecules, inhibiting MV +· Local enrichment reduces the probability of dimerization and other side reactions, thereby slowing down the change in electrolyte viscosity and optimizing mass transfer. (3) The uniformly dispersed porous carbon particles in the slurry can provide abundant and accessible catalytic active sites, enhancing the adsorption and catalytic effect on viologen compounds. Furthermore, the continuously updated reaction interface and shorter transport path in the slurry electrode help promote charge transfer and ion diffusion, reduce polarization, improve the reversibility of the two-electron reaction, and ultimately improve the battery energy density and rate performance. The negative electrode slurry of this invention achieves the suppression of side reactions, optimization of the mass transfer process, and improvement of battery performance. Attached Figure Description
[0020] Figure 1 This is a flowchart of the preparation of porous biochar in Example 1;
[0021] Figure 2 The pore size distribution diagram is shown for the porous biochar prepared in Example 1.
[0022] Figure 3 This is a scanning electron microscope image of the porous biochar prepared in Example 1.
[0023] Figure 4 This is a rheological property curve of the negative electrode slurry prepared in Example 1 before long-term cycling;
[0024] Figure 5This is a schematic diagram of the structure of the flow battery constructed according to the present invention;
[0025] Figure 6 This is a graph showing the rheological properties of the negative electrode slurry prepared in Example 1 after long-term cycling.
[0026] Figure 7 Charge-discharge curves of the flow battery constructed in Example 1;
[0027] Figure 8 The cycle efficiency curve of the flow battery constructed in Example 1;
[0028] Figure 9 Charge-discharge curves of the flow battery constructed in Example 2;
[0029] Figure 10 The cycle efficiency curve of the flow battery constructed in Example 2;
[0030] Figure 11 The charge-discharge curves of the flow battery constructed in Example 3 are shown.
[0031] Figure 12 The cycle efficiency curve of the flow battery constructed in Example 3;
[0032] Figure 13 The rheological properties of the negative electrode electrolyte prepared in Comparative Example 1 after long-term cycling are shown in the figure.
[0033] Figure 14 Charge-discharge curves of the flow battery constructed for Comparative Example 1;
[0034] Figure 15 The cycle efficiency curve of the flow battery constructed for Comparative Example 1;
[0035] Figure 16 Cycle efficiency curves of the flow battery constructed for Comparative Example 2;
[0036] Figure 17 Cyclic voltammetry test curves of the negative electrode slurries prepared in Example 1, Comparative Example 3, and Comparative Example 4;
[0037] Figure 18 Cycle efficiency curves of the flow battery constructed for Comparative Example 3;
[0038] Figure 19 The cycle efficiency curve of the flow battery constructed for Comparative Example 4. Detailed Implementation
[0039] Example 1
[0040] like Figure 1 As shown, the present invention provides a method for preparing porous carbon materials that are predominantly mesoporous and co-doped with phosphorus and oxygen, comprising the following steps:
[0041] (1) Take 20g of lignin, place it in a beaker, add 500mL of deionized water, stir and wash magnetically for 30min, and then discard the supernatant; repeat this washing process three times to fully remove water-soluble impurities; filter out the washed lignin and dry it in a vacuum oven at 105℃ for 24h; transfer the dried material to a planetary ball mill and grind it at 450 rpm for 3h, then pass it through a 140-mesh standard sieve, collect the sieve powder, and obtain the pretreated biomass raw material, denoted as C-0;
[0042] (2) Weigh 15g of the C-0 powder obtained in step (1) and place it together with 15g of analytical grade potassium hydroxide (KOH) powder (biomass: activator mass ratio of 1:1) in a beaker. Add 500mL of deionized water and stir magnetically for 30min. Then dry at 105℃ for 24h to obtain a mixture. Spread the mixture evenly in a ceramic boat and place it in the center of a tube furnace. Under a nitrogen atmosphere with a flow rate of 60sccm, heat it to 900℃ at a programmed heating rate of 5℃ / min and keep it at this temperature for 3h. After the tube furnace cools naturally to room temperature, take out the product and transfer it to a 200mL container. In the hydrochloric acid solution of M, the mixture was magnetically stirred in a constant temperature water bath at 60℃ for 12 hours to completely neutralize the alkaline substance. The solid product was collected by centrifugation (8000 rpm, 10 min) and repeatedly washed and centrifuged with a large amount of deionized water until the pH value of the supernatant was measured to be 7.0. The obtained product was dried at 105℃ for 24 hours to obtain a black powder, which is a multi-level porous biochar with mesoporous structure, denoted as C-1.
[0043] (3) Take 3 grams of the C-1 powder obtained in step (2) and mix it with 2.47 grams of analytical grade 1-hydroxyethylidene-1,1-diphosphonic acid (CAS 2000). 2809-21-4) The powder was mixed and added to a 50 mL solution of water and hydrogen peroxide aqueous solution (30 wt%) (volume ratio of water to hydrogen peroxide aqueous solution was 24:1). The mixture was stirred evenly and dried in a vacuum environment at 80 °C to obtain a dry powder mixture. The mixture was evenly spread in a ceramic boat and placed in the center of a tube furnace. Under a nitrogen atmosphere with a flow rate of 60 sccm, the mixture was heated to 900 °C at a programmed heating rate of 5 °C / min and kept at this temperature for 3 h. After the tube furnace cooled naturally to room temperature, the product was removed. It was transferred to 500 mL of deionized water and the solid product was collected by centrifugation (8000 rpm, 10 min). The product was repeatedly washed and centrifuged with a large amount of deionized water. Finally, the product was dried at 105 °C for 24 h to obtain about 2.0 g of black powder, which is a multi-level porous biochar with mesoporous structure and phosphorus and oxygen doping, denoted as PO-C.
[0044] The pore size distribution and morphological structure of the biochar prepared in Example 1 are as follows: Figure 2 , 3 As shown, through Figures 2-3 It can be seen that the biochar prepared in Example 1 exhibits a highly developed mesoporous network.
[0045] The negative electrode slurry of the present invention was prepared based on the biochar obtained in Example 1. Specifically, 10 mL of deionized water was added to a clean beaker, followed by 1.12 g of potassium chloride, 0.05 g of NaHCO3 as a pH modifier, and 0.03 g of xanthan gum as a dispersant. After complete dissolution, 1.90 g of 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen as the negative electrode active material was added, and finally 0.2 g of PO-C powder obtained in Example 1 was added. The mixture was pre-dispersed for 30 min at 8000 rpm using a high-speed shear disperser to form a uniform black suspension. The suspension was then transferred to an ultrasonic disperser with a circulating cooling water jacket and treated at 20 kHz and 400 W for 60 min to finally obtain a uniform, stable negative electrode slurry with good flowability.
[0046] The above-obtained negative electrode slurry was used to construct an aqueous viologen-based compound flow battery. The structure of the flow battery is as follows: Figure 5 As shown, the flow battery includes a positive electrode reservoir 1, a negative electrode reservoir 2, a peristaltic pump 3, a positive electrode reaction chamber 5, a negative electrode reaction chamber 6, a positive electrode current collector channel 7, and a negative electrode current collector channel 8 (made of impregnated graphite). The positive and negative electrode reaction chambers are connected to the reservoirs via pipes. The separator 4 is a pyridinized anion exchange membrane, which is soaked in a 1M KCl solution before use. Specifically, the membrane is soaked in a 1M KCl solution for 24 hours at room temperature to obtain KCl. + Thin film. 10 mL of the negative electrode slurry prepared in Example 1 was stored in negative electrode reservoir 2 (the negative electrode slurry was continuously bubbled with nitrogen for 10 min before testing to prevent oxygen oxidation), and the negative electrode slurry was transferred to negative electrode reaction chamber 6 via peristaltic pump 3; the positive electrode electrolyte (20 mL of 1.2 M potassium ferrocyanide solution containing 1.5 M potassium chloride as a supporting electrolyte) was stored in positive electrode reservoir 1 and transferred to positive electrode reaction chamber 5 via peristaltic pump 3. All battery tests were performed at room temperature on a LAND CT3002K battery test system, with the constant current charge / discharge current density set at 40 mA / cm². 2 The charging cutoff voltage is 2.0V, and the discharging cutoff voltage is 0.0V.
[0047] The rheological viscosity properties of the negative electrode slurry obtained by this invention are as follows: Figure 4 As shown, the slurry exhibits acceptable shear-thinning characteristics, meaning its viscosity decreases at higher shear rates, which is beneficial for stable transport by the flow electrode under actual cyclic conditions. Figure 4 and Figure 6 The comparison shows that the electrolyte viscosity did not change significantly after long cycling, indicating that the slurry suppressed side reactions such as dimerization and improved the long-cycle stability of the negative electrode active material.
[0048] pass Figures 7-8 It can be seen that the flow battery constructed in this invention has excellent performance, with an A / cm² value of 40 mA / cm². 2 It has a capacity of 27.0 Ah / L at a current density, a high capacity retention of 99.87% per cycle, an average energy efficiency of 71.66%, and can maintain high efficiency for 200 cycles.
[0049] Example 2
[0050] This invention relates to a method for preparing porous carbon materials that are predominantly mesoporous and phosphorus-doped, comprising the following steps:
[0051] (1) Take 20g of lignin, place it in a beaker, add 500mL of deionized water, stir and wash magnetically for 30min, and then discard the supernatant; repeat this washing process three times to fully remove water-soluble impurities; filter out the washed lignin and dry it in a vacuum oven at 105℃ for 24h; transfer the dried material to a planetary ball mill and grind it at 450 rpm for 3h, then pass it through a 140-mesh standard sieve, collect the sieve powder, and obtain the pretreated biomass raw material, denoted as C-0;
[0052] (2) Weigh 15g of the C-0 powder obtained in step (1) and place it together with 15g of analytical grade potassium hydroxide powder in a beaker. Add 500mL of deionized water and stir magnetically for 30min. Then dry the mixture at 105℃ for 24h. Spread the mixture evenly in a ceramic boat and place it in the center of a tube furnace. Under a nitrogen atmosphere with a flow rate of 60sccm, heat it to 900℃ at a programmed heating rate of 5℃ / min and pyrolyze it at this temperature for 3h. After the tube furnace cools naturally to room temperature, take out the product and transfer it to a 200mL container. In the hydrochloric acid solution of M, the mixture was magnetically stirred in a constant temperature water bath at 60℃ for 12 hours to completely neutralize the alkaline substance. The solid product was collected by centrifugation (8000 rpm, 10 min) and repeatedly washed and centrifuged with a large amount of deionized water until the pH value of the supernatant was measured to be 7.0. The obtained product was dried at 105℃ for 24 hours to obtain a black powder, which is a multi-level porous biochar with mesoporous structure, denoted as C-1.
[0053] (3) Take 3 grams of C-1 powder obtained in step (2), mix it with 2.47 grams of analytical grade 1-hydroxyethylidene-1,1-diphosphonic acid powder, add it to 50 mL of water, stir evenly, and dry it in a vacuum environment at 80 °C to obtain a dry mixture powder; spread the mixture evenly in a ceramic boat, place it in the center of a tube furnace, and heat it to 900 °C at a programmed heating rate of 5 °C / min under a nitrogen atmosphere with a flow rate of 60 sccm, and keep it at this temperature for 3 h for constant temperature pyrolysis; after the tube furnace cools naturally to room temperature, take out the product; transfer it to 500 mL of deionized water, collect the solid product by centrifugation (8000 rpm, 10 min), and repeatedly wash and centrifuge it with a large amount of deionized water. Finally, dry the obtained product at 105 °C for 24 h to obtain about 2.0 g of black powder, which is a multi-level porous biochar with mesoporous structure and phosphorus and oxygen doping, denoted as PC.
[0054] The negative electrode slurry was prepared based on the biochar obtained in Example 2. Specifically, 10 mL of deionized water was added to a clean beaker, followed by 1.12 g of potassium chloride, 0.05 g of NaHCO3 as a pH modifier, and 0.03 g of xanthan gum as a dispersant. After complete dissolution, 1.90 g of 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen was added as the negative electrode active material. Finally, 0.2 g of PC powder obtained in Example 2 was added. The mixture was pre-dispersed for 30 min at 8000 rpm using a high-speed shear disperser to form a uniform black suspension. The suspension was then transferred to an ultrasonic disperser with a circulating cooling water jacket and treated at 20 kHz and 400 W for 60 min to obtain a uniform, stable negative electrode slurry with good flowability.
[0055] The above-obtained negative electrode slurry was used to construct an aqueous viologen-based compound flow battery. The structure of the flow battery is as follows: Figure 5 As shown, the flow battery includes a positive electrode reservoir 1, a negative electrode reservoir 2, a peristaltic pump 3, a positive electrode reaction chamber 5, a negative electrode reaction chamber 6, a positive electrode current collector channel 7, and a negative electrode current collector channel 8 (made of impregnated graphite). The positive and negative electrode reaction chambers are connected to the reservoirs via pipes. The separator 4 is a pyridinized anion exchange membrane, which is soaked in a 1M KCl solution before use. Specifically, the membrane is soaked in a 1M KCl solution for 24 hours at room temperature to obtain KCl. +Thin film. 10 mL of the negative electrode slurry prepared in Example 2 was stored in negative electrode reservoir 2 (the negative electrode slurry was continuously bubbled with nitrogen for 10 min before testing to prevent oxygen oxidation), and the negative electrode slurry was transferred to negative electrode reaction chamber 6 via peristaltic pump 3; the positive electrode electrolyte (the positive electrode electrolyte was 20 mL of 1.2 M potassium ferrocyanide solution containing 1.5 M potassium chloride as a supporting electrolyte) was stored in positive electrode reservoir 1 and transferred to positive electrode reaction chamber 5 via peristaltic pump 3. All battery tests were performed at room temperature on a LAND CT3002K battery test system, with the constant current charge / discharge current density set at 40 mA / cm². 2 The charging cutoff voltage is 2.0V, and the discharging cutoff voltage is 0.0V.
[0056] pass Figures 9-10 It can be seen that the flow battery constructed in this invention operates at 40 mA / cm². 2 It has a capacity of 26.4 Ah / L at a current density, a high capacity retention of 99.85% per cycle, an average energy efficiency of 65.65%, and can maintain high efficiency for 200 cycles.
[0057] Example 3
[0058] This invention relates to a method for preparing porous carbon materials that are predominantly mesoporous and oxygen-doped, comprising the following steps:
[0059] (1) Take 20g of lignin, place it in a beaker, add 500mL of deionized water, stir and wash magnetically for 30min, and then discard the supernatant; repeat this washing process three times to fully remove water-soluble impurities; filter out the washed lignin and dry it in a vacuum oven at 105℃ for 24h; transfer the dried material to a planetary ball mill and grind it at 450 rpm for 3h, then pass it through a 140-mesh standard sieve, collect the sieve powder, and obtain the pretreated biomass raw material, denoted as C-0;
[0060] (2) Weigh 15g of the C-0 powder obtained in step (1), and place it together with 15g of analytical grade potassium hydroxide powder in a beaker. Add 500mL of deionized water to the beaker, stir magnetically for 30min, and dry at 105℃ for 24h to obtain a mixture. Spread the mixture evenly in a ceramic boat and place it in the center of a tube furnace. Under a nitrogen atmosphere with a flow rate of 60sccm, heat it to 900℃ at a programmed heating rate of 5℃ / min, and keep it at this temperature for 3h. After the tube furnace cools naturally to room temperature, take out the product. Transfer it to 200mL of a ceramic boat and 200mL of a ceramic boat. In the hydrochloric acid solution of M, the mixture was magnetically stirred in a constant temperature water bath at 60℃ for 12 hours to completely neutralize the alkaline substance. The solid product was collected by centrifugation (8000 rpm, 10 min) and repeatedly washed and centrifuged with a large amount of deionized water until the pH value of the supernatant was measured to be 7.0. The obtained product was dried at 105℃ for 24 hours to obtain a black powder, which is a multi-level porous biochar with mesoporous structure, denoted as C-1.
[0061] (3) Take 3 grams of C-1 powder obtained in step (2) and add it to a mixed solution of 50 mL of water and hydrogen peroxide aqueous solution (30 wt%) (the volume ratio of water to hydrogen peroxide aqueous solution is 24:1). Dry it in a vacuum environment at 80 °C to obtain a dry mixed powder. Spread the mixture evenly in a ceramic boat and place it in the center of a tube furnace. Under the protection of a nitrogen atmosphere with a flow rate of 60 sccm, heat it to 900 °C at a programmed heating rate of 5 °C / min and keep it at this temperature for 3 h. After the tube furnace cools naturally to room temperature, take out the product. Transfer it to 500 mL of deionized water and collect the solid product by centrifugation (8000 rpm, 10 min). Repeatedly wash and centrifuge with a large amount of deionized water. Finally, dry the obtained product at 105 °C for 24 h to obtain about 2.0 g of black powder, which is a multi-level porous biochar with mesoporous structure and phosphorus and oxygen doping, denoted as OC.
[0062] The negative electrode slurry was prepared based on the biochar obtained in Example 3. Specifically, 10 mL of deionized water was added to a clean beaker, followed by 1.12 g of potassium chloride, 0.05 g of NaHCO3 as a pH modifier, and 0.03 g of xanthan gum as a dispersant. After complete dissolution, 1.90 g of 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen as the negative electrode active material was added. Finally, 0.2 g of OC powder obtained in Example 3 was added. The mixture was pre-dispersed for 30 min at 8000 rpm using a high-speed shear disperser to form a uniform black suspension. The suspension was then transferred to an ultrasonic disperser with a circulating cooling water jacket and treated at 20 kHz and 400 W for 60 min to obtain a uniform, stable negative electrode slurry with good flowability.
[0063] The above-obtained negative electrode slurry was used to construct an aqueous viologen-based compound flow battery. The structure of the flow battery is as follows: Figure 5 As shown, the flow battery includes a positive electrode reservoir 1, a negative electrode reservoir 2, a peristaltic pump 3, a positive electrode reaction chamber 5, a negative electrode reaction chamber 6, a positive electrode current collector channel 7, and a negative electrode current collector channel 8 (made of impregnated graphite). The positive and negative electrode reaction chambers are connected to the reservoirs via pipes. The separator 4 is a pyridinized anion exchange membrane, which is soaked in a 1M KCl solution before use. Specifically, the membrane is soaked in a 1M KCl solution for 24 hours at room temperature to obtain KCl. + Thin film. 10 mL of the negative electrode slurry prepared in Example 3 was stored in negative electrode reservoir 2 (the negative electrode slurry was continuously bubbled with nitrogen for 10 min before testing to prevent oxygen oxidation), and the negative electrode slurry was transferred to negative electrode reaction chamber 6 via peristaltic pump 3; the positive electrode electrolyte (the positive electrode electrolyte was 20 mL of 1.2 M potassium ferrocyanide solution containing 1.5 M potassium chloride as a supporting electrolyte) was stored in positive electrode reservoir 1 and transferred to positive electrode reaction chamber 5 via peristaltic pump 3. All battery tests were performed at room temperature on a LAND CT3002K battery test system, with the constant current charge / discharge current density set at 40 mA / cm². 2 The charging cutoff voltage is 2.0V, and the discharging cutoff voltage is 0.0V.
[0064] pass Figures 11-12 It can be seen that the flow battery constructed in this invention operates at 40 mA / cm². 2 It has a capacity of 27.6 Ah / L at a current density, a high capacity retention of 99.81% per cycle, an average energy efficiency of 64.70%, and can maintain high efficiency for 200 cycles.
[0065] Comparative Example 1
[0066] Comparative Example 1 uses graphite felt, a commonly used electrode material in flow batteries. The difference between the flow battery in Comparative Example 1, based on traditional graphite felt, and the flow battery in Example 1 is as follows: Example 1 uses a negative electrode slurry; while the traditional graphite felt in Comparative Example 1 is pretreated and placed in the current collector channel 8 during flow battery assembly. The negative electrode electrolyte is prepared by mixing potassium chloride, NaHCO3, and 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen in 10 mL of water and stirring until completely dissolved. The negative electrode electrolyte contains 1.5 M KCl as the supporting electrolyte, 0.06 M NaHCO3 as the pH modifier, and 0.6 M 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen as the active material. Because the voltage polarization of the flow battery assembled with traditional graphite felt is relatively large, the charging cutoff voltage is increased to 2.3 V to demonstrate the two-electron transfer of viologen-type active materials.
[0067] Comparative Example 1 illustrates a traditional pretreatment method for graphite felt, specifically as follows: Commercial graphite felt was prepared and cut into 2cm × 2cm × 0.5cm blocks. The graphite felt was placed in a beaker, and 100mL of deionized water was added. The mixture was magnetically stirred and washed for 30 minutes to thoroughly remove surface dust and soluble impurities. Subsequently, ultrasonic cleaning was performed for 30 minutes to further remove contaminants adhering to the pores and fiber surfaces. Ultrasonic cleaning was then repeated for 30 minutes with anhydrous ethanol to remove organic residues. The cleaned graphite felt was then dried in a vacuum oven at 105℃ for 12 hours and cooled to room temperature before use.
[0068] Comparative Example 1: The flow battery structure is the same as in Example 1. The flow battery includes a positive electrode reservoir 1, a negative electrode reservoir 2, a peristaltic pump 3, a positive electrode reaction chamber 5, a negative electrode reaction chamber 6, a positive electrode current collector channel 7 (made of impregnated graphite), and a conventional graphite felt electrode 8. The positive and negative electrode reaction chambers are connected to the reservoirs via pipes. The separator 4 is a pyridinized anion exchange membrane, which is soaked in a 1M KCl solution before use. Specifically, the membrane is soaked in a 1M KCl solution for 24 hours at room temperature to obtain KCl. + Thin film. 10 mL of the negative electrode electrolyte prepared in Comparative Example 1 was stored in negative electrode reservoir 2 (the negative electrode electrolyte was bubbled with nitrogen for 10 min before the test to prevent oxygen oxidation), and the negative electrode electrolyte was transferred to negative electrode reaction chamber 6 by peristaltic pump 3; positive electrode electrolyte (the positive electrode electrolyte is 20 mL of 1.2 M potassium ferrocyanide solution, which contains 1.5 M potassium chloride as supporting electrolyte) was stored in positive electrode reservoir 1 and transferred to positive electrode reaction chamber 5 by peristaltic pump 3.
[0069] pass Figure 13 Rheological viscosity analysis of the negative electrode electrolyte after cycling showed a significant change in viscosity compared to Example 1, indicating severe side reactions such as dimerization and a marked increase in intermolecular forces. Figures 14-15 It can be seen that the performance of traditional fixed graphite felt is relatively poor, at 40mA / cm 2 It has a capacity of only 25.6 Ah / L at a current density, a capacity retention of 98.73% per cycle, an average energy efficiency of 52.86%, and can only cycle stably for 50 cycles.
[0070] Comparative Example 2
[0071] A method for preparing porous carbon materials includes the following steps:
[0072] (1) Take 20g of lignin, place it in a beaker, add 500mL of deionized water, stir and wash magnetically for 30min, and then discard the supernatant; repeat this washing process three times to fully remove water-soluble impurities; filter out the washed lignin and dry it in a vacuum oven at 105℃ for 24h; transfer the dried material to a planetary ball mill and grind it at 450 rpm for 3h, then pass it through a 140-mesh standard sieve, collect the sieve powder, and obtain the pretreated biomass raw material, denoted as C-0;
[0073] (2) Weigh 15g of the C-0 powder obtained in step (1), and place it together with 15g of analytical grade potassium hydroxide powder in a beaker. Add 500mL of deionized water to the beaker, stir magnetically for 30min, and dry at 105℃ for 24h to obtain a mixture. Spread the mixture evenly in a ceramic boat and place it in the center of a tube furnace. Under a nitrogen atmosphere with a flow rate of 60sccm, heat it to 900℃ at a programmed heating rate of 5℃ / min, and keep it at this temperature for 3h. After the tube furnace cools naturally to room temperature, take out the product. Transfer it to 200mL of a ceramic boat and 200mL of a ceramic boat. In the hydrochloric acid solution of M, the mixture was magnetically stirred in a constant temperature water bath at 60℃ for 12 hours to completely neutralize the alkaline substances. The solid product was collected by centrifugation (8000 rpm, 10 min) and repeatedly washed and centrifuged with a large amount of deionized water until the pH value of the supernatant was measured to be 7.0. The obtained product was dried at 105℃ for 24 hours to obtain a black powder, which is a multi-level porous biochar with mesoporous structure, denoted as C-1.
[0074] The negative electrode slurry was prepared based on the biochar obtained in Comparative Example 2. Specifically, 10 mL of deionized water was added to a clean beaker, followed by 1.12 g of potassium chloride, 0.05 g of NaHCO3 as a pH modifier, and 0.03 g of xanthan gum as a dispersant. After complete dissolution, 1.90 g of 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen was added as the negative electrode active material. Finally, 0.2 g of C-1 powder obtained in Comparative Example 2 was added. The mixture was pre-dispersed for 30 min at 8000 rpm using a high-speed shear disperser to form a uniform black suspension. The suspension was then transferred to an ultrasonic disperser with a circulating cooling water jacket and treated at 20 kHz and 400 W for 60 min to obtain a uniform, stable negative electrode slurry with good flowability.
[0075] The above-obtained negative electrode slurry was used to construct an aqueous viologen-based compound flow battery. The structure of the flow battery is as follows: Figure 5As shown, the flow battery includes a positive electrode reservoir 1, a negative electrode reservoir 2, a peristaltic pump 3, a positive electrode reaction chamber 5, a negative electrode reaction chamber 6, a positive electrode current collector channel 7, and a negative electrode current collector channel 8 (made of impregnated graphite). The positive and negative electrode reaction chambers are connected to the reservoirs via pipes. The separator 4 is a pyridinized anion exchange membrane, which is soaked in a 1M KCl solution before use. Specifically, the membrane is soaked in a 1M KCl solution for 24 hours at room temperature to obtain KCl. + Thin film. 10 mL of the negative electrode slurry prepared in Comparative Example 2 was stored in negative electrode reservoir 2 (the negative electrode slurry was continuously bubbled with nitrogen for 10 min before testing to prevent oxygen oxidation). The negative electrode slurry was transferred to negative electrode reaction chamber 6 via peristaltic pump 3. The positive electrode electrolyte (20 mL of 1.2 M potassium ferrocyanide solution containing 1.5 M potassium chloride as a supporting electrolyte) was stored in positive electrode reservoir 1 and transferred to positive electrode reaction chamber 5 via peristaltic pump 3. All battery tests were performed at room temperature on a LAND CT3002K battery test system, with the constant current charge / discharge current density set at 40 mA / cm². 2 The charging cutoff voltage is 2.0V, and the discharging cutoff voltage is 0.0V.
[0076] pass Figure 16 It can be seen that the flow battery constructed in Comparative Example 2 operates at 40 mA / cm². 2 At current density, it has an average energy efficiency of only 48.58% and can only cycle 125 times.
[0077] Comparative Example 3
[0078] The negative electrode slurry of the present invention was prepared based on the biochar obtained in Example 1. Specifically, 10 mL of deionized water was added to a clean beaker, followed by 1.12 g of potassium chloride, 0.05 g of NaHCO3 as a pH modifier, and 0.03 g of xanthan gum as a dispersant. After complete dissolution, 1.90 g of 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen as the negative electrode active material was added, and finally 0.1 g of PO-C powder obtained in Example 1 was added. The mixture was pre-dispersed for 30 min at 8000 rpm using a high-speed shear disperser to form a uniform black suspension. The suspension was then transferred to an ultrasonic disperser with a circulating cooling water jacket and treated for 60 min at 20 kHz and 400 W power to finally obtain a uniform, stable negative electrode slurry with good flowability.
[0079] The above-obtained negative electrode slurry was used to construct an aqueous viologen-based compound flow battery. The structure of the flow battery is as follows: Figure 5As shown, the flow battery includes a positive electrode reservoir 1, a negative electrode reservoir 2, a peristaltic pump 3, a positive electrode reaction chamber 5, a negative electrode reaction chamber 6, a positive electrode current collector channel 7, and a negative electrode current collector channel 8 (made of impregnated graphite). The positive and negative electrode reaction chambers are connected to the reservoirs via pipes. The separator 4 is a pyridinized anion exchange membrane, which is soaked in a 1M KCl solution before use. Specifically, the membrane is soaked in a 1M KCl solution for 24 hours at room temperature to obtain KCl. + Thin film. 10 mL of the negative electrode slurry prepared in Comparative Example 3 was stored in negative electrode reservoir 2 (the negative electrode slurry was continuously bubbled with nitrogen for 10 min before testing to prevent oxygen oxidation). The negative electrode slurry was transferred to negative electrode reaction chamber 6 via peristaltic pump 3. The positive electrode electrolyte (20 mL of 1.2 M potassium ferrocyanide solution containing 1.5 M potassium chloride as a supporting electrolyte) was stored in positive electrode reservoir 1 and transferred to positive electrode reaction chamber 5 via peristaltic pump 3. All battery tests were performed at room temperature on a LAND CT3002K battery test system, with the constant current charge / discharge current density set at 40 mA / cm². 2 The charging cutoff voltage is 2.0V, and the discharging cutoff voltage is 0.0V.
[0080] pass Figures 17-18 It can be seen that due to insufficient addition of porous biochar in the negative electrode slurry, a good conductive network was not constructed, resulting in large ohmic polarization of the battery and poor performance of the flow battery, with a performance of 40 mA / cm. 2 It has an average energy efficiency of only 20.92% at current density and can only cycle 100 times.
[0081] Comparative Example 4
[0082] The negative electrode slurry of the present invention was prepared based on the biochar obtained in Example 1. Specifically, 10 mL of deionized water was added to a clean beaker, followed by 1.12 g of potassium chloride, 0.05 g of NaHCO3 as a pH modifier, and 0.03 g of xanthan gum as a dispersant. After complete dissolution, 1.90 g of 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen as the negative electrode active material was added, and finally 0.3 g of PO-C powder obtained in Example 1 was added. The mixture was pre-dispersed for 30 min at 8000 rpm using a high-speed shear disperser to form a uniform black suspension. The suspension was then transferred to an ultrasonic disperser with a circulating cooling water jacket and treated for 60 min at 20 kHz and 400 W power to finally obtain a uniform, stable negative electrode slurry with good flowability.
[0083] The above-obtained negative electrode slurry was used to construct an aqueous viologen-based compound flow battery. The structure of the flow battery is as follows: Figure 5As shown, the flow battery includes a positive electrode reservoir 1, a negative electrode reservoir 2, a peristaltic pump 3, a positive electrode reaction chamber 5, a negative electrode reaction chamber 6, a positive electrode current collector channel 7, and a negative electrode current collector channel 8 (made of impregnated graphite). The positive and negative electrode reaction chambers are connected to the reservoirs via pipes. The separator 4 is a pyridinized anion exchange membrane, which is soaked in a 1M KCl solution before use. Specifically, the membrane is soaked in a 1M KCl solution for 24 hours at room temperature to obtain KCl. + Thin film. 10 mL of the negative electrode slurry prepared in Comparative Example 4 was stored in negative electrode reservoir 2 (the negative electrode slurry was continuously bubbled with nitrogen for 10 min before testing to prevent oxygen oxidation). The negative electrode slurry was transferred to negative electrode reaction chamber 6 via peristaltic pump 3. The positive electrode electrolyte (20 mL of 1.2 M potassium ferrocyanide solution containing 1.5 M potassium chloride as a supporting electrolyte) was stored in positive electrode reservoir 1 and transferred to positive electrode reaction chamber 5 via peristaltic pump 3. All battery tests were performed at room temperature on a LAND CT3002K battery test system, with the constant current charge / discharge current density set at 40 mA / cm². 2 The charging cutoff voltage is 2.0V, and the discharging cutoff voltage is 0.0V.
[0084] pass Figure 17 , 19 It can be seen that due to the excessive addition of porous biochar in the negative electrode slurry, the slurry becomes too viscous, resulting in poor cycle flow performance and large concentration polarization, leading to poor performance of the flow battery at 40 mA / cm². 2 It has an average energy efficiency of only 52.91% at current density and can only cycle 100 times.
[0085] This invention addresses the problems of low catalytic activity and easy clogging of viscous electrolyte circulation in existing flow batteries with fixed carbon felt. By introducing non-metallic doped porous carbon materials to construct a high-performance negative electrode slurry system, this invention solves the problems of poor catalytic activity of traditional carbon materials, severe shuttle effect of viologen compounds, and insufficient long-cycle stability, significantly improving the energy density, cycle stability, and electrochemical reaction efficiency of flow batteries.
Claims
1. A water-based viologen-based compound flow battery negative electrode slurry, characterized in that: It is prepared by mixing non-metallic doped porous carbon material, viologen-like compounds, supporting electrolyte, pH modifier and dispersant in an aqueous medium; the non-metallic doped porous carbon material is phosphorus-doped porous carbon material, oxygen-doped porous carbon material or phosphorus-oxygen co-doped porous carbon material.
2. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 1, characterized in that: In the negative electrode slurry, the molar concentration of the viologen compound is 0.6~1.0M; the molar concentration of the supporting electrolyte is 1.0~1.5M; the molar concentration of the pH modifier is 0.05~0.06M; the dispersant accounts for 0.3~0.5wt% of the aqueous medium mass; and the non-metallic doped porous carbon material accounts for 1.5~2.5wt% of the aqueous medium mass.
3. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 1, characterized in that: The viologen compound is 1,1'-bis(2-hydroxyethyl)-4,4'-bipyridine viologen or methyl viologen; the supporting electrolyte is KCl or NaCl; the dispersant is xanthan gum; and the pH modifier is NaHCO3.
4. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 1, characterized in that: The ultrasonic time during the preparation of the slurry is 60-80 minutes, and the ultrasonic power is 300-400W.
5. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 1, characterized in that: The non-metal-doped porous carbon material is prepared by the following method, including the following steps: (1) Wash, crush, sieve and dry the waste biomass to obtain biomass raw material that has lost its surface water; (2) The obtained biomass raw materials are mixed with activator and carbonized under inert gas protection. After treatment, the raw materials are washed and dried to obtain porous biochar. (3) The porous biochar is mixed with a non-metallic dopant source and added to water. It is first dried in a vacuum environment and then carbonized at high temperature under inert gas protection. After carbonization, it is washed and dried to obtain a non-metallic doped porous carbon material.
6. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 5, characterized in that: In step (1), the waste biomass is one of lignin, macadamia nut shells, coconut shells, peanut shells, or walnut shells.
7. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 5, characterized in that: In step (1), the drying temperature is 105~110℃ and the sieve mesh size is 100~200 mesh.
8. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 5, characterized in that: In step (2), the activator is one of KOH, KHCO3 or KCl; the mass ratio of the activator to the biomass is 1:0.5~1.
9. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 5, characterized in that: In step (3), the non-metallic dopant source is 1-hydroxyethylidene-1,1-diphosphonic acid and / or hydrogen peroxide; and the mass ratio of the non-metallic dopant source to the porous biochar is 0.22~1.05:
1.
10. The aqueous viologen-based compound flow battery negative electrode slurry according to claim 5, characterized in that: In steps (2) to (3), the carbonization temperature is 850 to 900°C and the carbonization time is 3 to 4 hours.
